The Effect of Diabetes Self-Management Education on Body Weight, Glycemic Control, and Other Metabolic Markers in Patients with Type 2 Diabetes Mellitus - Chuang Yuan; Christopher W. K. Lai; Lawrence W. C. Chan; Meyrick Chow; Helen K. W. Law; Michael Ying (Journal of Diabetes Research)
Aims. To comprehensively evaluate the effect of a short-term diabetes self-management education (DSME) on metabolic markers and atherosclerotic parameters in patients with type 2 diabetes. Methods. 76 patients with type 2 diabetes were recruited in this study. They were divided into the intervention group (n=36) and control group (n=40). The patients in the intervention group received a 3-month intervention, including an 8-week education on self-management of diabetes mellitus and subsequent 4 weeks of practice of the self-management guidelines. The patients in the control group received standard advice on medical nutrition therapy. Metabolic markers, carotid intima-media thickness (CIMT), and carotid arterial stiffness (CAS) of the patients in both groups were assessed before and after the 3-month intervention. Results. There was a significant reduction in hemoglobin A1c (HbA1c, -0.2±0.56% versus 0.08±0.741%; P<0.05) and body weight (-1.19±1.39 kg versus -0.61±2.04 kg; P<0.05) in the intervention group as compared to the control group. However, no significant improvements were found in other metabolic markers, CIMT and CAS (P>0.05). Conclusions. DSME can improve HbA1c and body weight in patients with type 2 diabetes.